KOMUNIKASI LINGKUNGAN DALAM PROGRAM MITIGASI KEBAKARAN HUTAN DAN LAHAN PT KILANG PERTAMINA INTERNASIONAL REFINERY UNIT II PRODUKSI SUNGAI PAKNING - Asri Dewi; Yasir; Anuar Rasyid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Forest and land fires have long been a source of public concern, particularly due to the frequent occurrence of peatland fires in Riau Province. Various institutions have undertaken efforts to address this disaster, including PT KPI RU II Sungai Pakning, which implements a community empowerment program focused on community-based forest and land fire mitigation through the Masyarakat Peduli Bencana (MPB) initiative. This study employs a qualitative research approach and focuses on the environmental communication process carried out by the Community Development Officer (CDO) team in implementing the community-based fire mitigation program. The findings reveal that the CDO team applies stages of environmental communication planning, production, implementation, and evaluation in executing the empowerment program. Through these stages, the program contributes to behavioral changes within the community toward greater environmental awareness and sustainable peatland management and improve environmental education.